THE IMPLEMENTATION OF D PHASE MERDEKA CURRICULUM IN THE ENGLISH TEXTBOOK - Putri, Tara Andina; Amin, Syarif; Syarif, Andi Rachmawati (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to conduct a content analysis of the English textbook